2016
DOI: 10.1063/1.4946397
|View full text |Cite
|
Sign up to set email alerts
|

Sodium-ion-conducting polymer nanocomposite electrolyte of TiO2/PEO/PAN complexed with NaPF6

Abstract: A free standing transparent film of solid state polymer electrolyte based on PEO/PAN + NaPF6 with different compositions of nano sized TiO2 in weight percent (x = 0, 1, 2, 5, 10, 15, 20 ) is synthesized by using standard solution cast technique. The homogeneous surface of above polymer composition is examined by FESEM. The microscopic interaction among polymer, salt and nanoceramic filler has been analyzed by Fourier Transformed Infra-Red (FTIR) spectroscopy. The reduction of ion pair formation in polymeric s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…The common polymer matrices for SSE are PEO, poly(vinylidene fluoride) (PVDF), poly(vinylidene fluoride-co-hexafluoropropylene) (PVDF-HFP), poly(acrylonitrile), and poly(methacrylate). [95][96][97][98][99] The additive salts mainly contain NaPF 6 , NaClO 4 , (NaFSI). The main problems of most polymer electrolyte are low ionic conductivity (<10 À4 S cm À1 ) at room temperature and unsatisfactory Na + -ion transference number (less than 0.5).…”
Section: Organic Electrolytementioning
confidence: 99%
See 2 more Smart Citations
“…The common polymer matrices for SSE are PEO, poly(vinylidene fluoride) (PVDF), poly(vinylidene fluoride-co-hexafluoropropylene) (PVDF-HFP), poly(acrylonitrile), and poly(methacrylate). [95][96][97][98][99] The additive salts mainly contain NaPF 6 , NaClO 4 , (NaFSI). The main problems of most polymer electrolyte are low ionic conductivity (<10 À4 S cm À1 ) at room temperature and unsatisfactory Na + -ion transference number (less than 0.5).…”
Section: Organic Electrolytementioning
confidence: 99%
“…Co-polymerization, blending, crosslinking, and combination with plasticizers are proven to be effective in achieving the goal. 12,[95][96][97][98][99][100][101][102] For instance, our group fabricated quasi-SSE composed of PVDF-HFP matrix with SiO 2 and NaClO 4 -TEGDME (tetraethylene glycol dimethyl ether) additives ( Figure 6A). 95 The ionic conductivity of the electrolyte can reach as high as 10 À3 S cm À1 at room temperature.…”
Section: Organic Electrolytementioning
confidence: 99%
See 1 more Smart Citation
“…When the nano-TiO 2 content was 5 wt %, the SPE with the ratio of EO/Na = 20:1 showed a maximum ionic conductivity of 2.62 × 10 –4 S cm –1 at 60 °C (Figure c). In addition, a free-standing SPE film based on PEO/PAN + NaPF 6 with different dosages of nano-TiO 2 was fabricated by Sharma’s group . The results indicated that the as-prepared (PEO/PAN) 20 + NaPF 6 + 15 wt % TiO 2 composite film exhibited optimized ionic conductivity of 1.8 × 10 –4 S cm –1 .…”
Section: Classificiation and Ion Transport Mechanism Of Solid-state E...mentioning
confidence: 99%